(untitled) (Revista de Ciências Agroveterinárias, 2024)
White oat (Avena sativa L.) is the winter cereal with the highest nutritional quality, offering multifunctional characteristics due to its benefits to human health, animal nutrition and soil cover. In this way, this crop is highly valued in society. The aim of this study were to evaluate agronomic performance and verify whether there is genetic variability in recombinant and mutant segregating progenies of white oat. The study was conducted at Escola Fazenda UNIJUI (IRDeR), located in the municipality of Augusto Pestana, in the state of Rio Grande do Sul, Brazil. The experimental design used followed an augmented block with interspersed controls. A total of 460 white oat progenies were sown and the intercrop control was represented by the cultivar URS Taura, arranged in three replications. The collected data were subjected to descriptive analysis to identify the number of informative progenies and the maximum, minimum, and average values for the measured variables. Frequency distribution graphs of characters with continuous distribution were generated, stratified by mutant and recombinant progenies. Based on the data obtained, a Bayesian approach was used with generalized mixed models through Monte Carlo and Markov Chains (MCMC). With this information, the genetic (VCV) and phenotypic variance components were estimated with significance based on the 5% probability by χ² (pMCMC). Afterwards, Euclidean distances were calculated and the distance dendrogram was carried out using the UPGMA clustering algorithm. Pearson’s linear correlation coefficients were calculated between pairs of variables, with significance verified by the t test at 5% probability. The mutant progenies have greater tillering capacity, while the recombinant progenies have greater tolerance to diseases and lower natural grain threshing. There is a clear genetic variability between recombinant and mutant progenies for the evaluated characters.